Laboratory efficacy of rhamnolipid produced by Pseudomonas aeruginosa USM-AR2 as biopesticide against bagworm, Metisa plana walker (Lepidoptera: Psychidae) - Mohd Zaludin, Muhammad Syafiq; Wan Abdul Ghani, Wan Mohd Hafezul; Nasir, Mohd Shafiq; Mohd Yahya, Ahmad Ramli; Md Noh, Nur Asshifa; Salim, Hasber (Universiti Kebangsaan Malaysia, 2021)
The bagworm, Metisa plana Walker (Lepidoptera: Psychidae) is one of the major pests causes defoliation of oil palm leaves, resulting in severe yield loss of oil palm production. In this study, rhamnolipid, a biosurfactant produced by Pseudomonas aeruginosa USM-AR2, was tested for its effectiveness in causing mortality of bagworms. A total of 13 treatments were tested, namely mixtures of different doses of rhamnolipid and neem oil as well as cypermethrin, as chemical insecticides that are commonly used in oil palm plantations, to control bagworms. The results showed that the mixture of 200 ppm rhamnolipid and 30000 ppm neem oil, and a single treatment of 30000 ppm neem oil recorded 83.33% mortality at five days after treatment (DAT). The chemical insecticide treatment by cypermethrin recorded 100% mortality at 2 DAT. The lowest efficacy was observed on the mixture of 100 ppm rhamnolipid and 10000 ppm neem oil, producing 50% at 5 DAT and 73.33% of mortality at the end of the observation. Probit analyses showed that the LT50 score for single treatment of rhamnolipid of 100ppm and 200ppm were 5.22 DAT and 4.61 DAT. Meanwhile, the LT90 scores for 100ppm and 200ppm rhamnolipid were 13.08 DAT and 11.07 DAT respectively.